LEVERAGING VLOGS INTEGRATION FOR ENGLISH LANGUAGE TEACHING: A SYSTEMATIC REVIEW - Siti Nopita; Putri Pujiyawati; Naf’an Tarihoran (Adisam Publisher, 2025)
This study examines the effectiveness of integrating video blogs (vlogs) into English Language Teaching (ELT) to enhance students' speaking abilities. A systematic review was conducted following the PRISMA framework, analyzing articles published between 2020 and 2025 from databases such as Google Scholar and Publish or Perish. The study investigates how vlogs influence students' speaking confidence and fluency, the challenges they encounter in utilizing vlogs for language learning, and instructional strategies that can optimize vlog-based learning. The results reveal that vlogging fosters self-efficacy, vocabulary acquisition, and independent learning while promoting a collaborative and student-centered environment. Additionally, topic-based vlogs have been found to enhance students' grammar and confidence in speaking. However, challenges such as informal language use, technological limitations, and digital competence barriers remain prevalent. The findings of this study suggest that while vlogs contribute positively to speaking skill development, educators must address content quality, technological accessibility, and students' adaptation to digital learning tools to maximize their effectiveness in ELT.